PROPER TRAINING CAN PRODUCE BETTER PROJECT MANAGEMENT, SAYS USM VC - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 11 May 2015 ASEAN countries can expect better project management in the near future, thanks to a collaborative programme organised by Universiti Sains Malaysia’s Centre for Innovation and Productivity in Public Administration (PiPPA USM) in collaboration with the Asian Development Bank (ADB), Brunei DarussalamIndonesiaMalaysiaPhilippines East ASEAN Growth Area (BIMPEAGA) and the IndonesiaMalaysiaThailand Growth Triangle (IMTGT).